2003
DOI: 10.2460/ajvr.2003.64.1021
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of acute-phase proteins in dogs with leishmaniosis during short-term treatment

Abstract: Measurement of concentrations of selected acute-phase proteins, such as C-reactive protein or ceruloplasmin, could be used to evaluate the initial response of dogs with leishmaniosis to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
77
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 23 publications
8
77
0
3
Order By: Relevance
“…These results are in agreement with previous reports in which a possible stimulation in the synthesis of this protein caused by different drugs such as antihelmintics (Tosa et al, 1993), meglumine antimoniate (Martinez-Subiela et al, 2003a), glucocorticoids and cytotoxic drugs (McGrotty et al, 2003) was suggested.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…These results are in agreement with previous reports in which a possible stimulation in the synthesis of this protein caused by different drugs such as antihelmintics (Tosa et al, 1993), meglumine antimoniate (Martinez-Subiela et al, 2003a), glucocorticoids and cytotoxic drugs (McGrotty et al, 2003) was suggested.…”
Section: Discussionsupporting
confidence: 83%
“…Among these, the index CRP*CP/Alb was selected as the optimum since it showed a greater and faster decrease (78% decrease on day 10) compared with the others. Moreover, the magnitude of the decrease of that index on day 10 was greater than that reported for individual acute phase proteins (44% for CRP and 58% for CP) (Martinez-Subiela et al, 2003a). This finding suggest that the combination of both positive acute phase proteins (CRP and Cp) with a negative one could have a greater potential as a biomarker to evaluate the early response to therapy in canine leishmaniasis compared to the individual proteins alone.…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations